Use of a Managed Solitary Bee to Pollinate Almonds: Population Sustainability and Increased Fruit Set - Jordi Bosch; Sergio Osorio-Canadas; Fabio Sgolastra; Narcís Vicens (Insects, 2021)
Osmia spp. are excellent orchard pollinators but evidence that their populations can be sustained in orchard environments and their use results in increased fruit production is scarce. We released an Osmia cornuta population in an almond orchard and measured its population dynamics, as well as visitation rates and fruit set at increasing distances from the nesting stations. Honeybees were 10 times more abundant than O. cornuta. However, the best models relating fruit set and bee visitation included only O. cornuta visitation, which explained 41% and 40% of the initial and final fruit set. Distance from the nesting stations explained 27.7% and 22.1% of the variability in initial and final fruit set. Of the 198 females released, 99 (54.4%) established and produced an average of 9.15 cells. Female population growth was 1.28. By comparing our results with those of previous O. cornuta studies we identify two important populational bottlenecks (female establishment and male-biased progeny sex ratios). Our study demonstrates that even a small population of a highly effective pollinator may have a significant impact on fruit set. Our results are encouraging for the use of Osmia managed populations and for the implementation of measures to promote wild pollinators in agricultural environments.